2002
DOI: 10.1080/13561820220104122
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessionality in health and social care: the Achilles' heel of partnership?

Abstract: Partnership working is now a central plank of public policy in the UK, especially in the field of health and social care. However, much of the policy thrust has been at the level of interorganisational working rather than at the level of interprofessional partnerships. The empirical and theoretical literature is largely sceptical about the feasibility of effective joint working between separate but related professionals--the 'pessimistic tradition'. Based upon an empirical study of general practitioners, commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
197
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(206 citation statements)
references
References 9 publications
6
197
1
1
Order By: Relevance
“…258 If so, these results would support suggestions that organisational restructuring alone is not a sufficient condition for overcoming barriers to developing integrated practice. 179,255,257,259 A wide range of studies on service integration have suggested that organisational change and instability can hinder joint working, 50,225,260 but this is not supported by our analysis which found that teams that had faced major organisational change in the preceding 12 months were no more or less integrated than other teams. Features that seemed to be more important included the location of the team base and the discipline of the team manager, although, interestingly, no previous work seems to have considered these.…”
Section: Community Mental Health Teams For Older People: a National Scontrasting
confidence: 55%
“…258 If so, these results would support suggestions that organisational restructuring alone is not a sufficient condition for overcoming barriers to developing integrated practice. 179,255,257,259 A wide range of studies on service integration have suggested that organisational change and instability can hinder joint working, 50,225,260 but this is not supported by our analysis which found that teams that had faced major organisational change in the preceding 12 months were no more or less integrated than other teams. Features that seemed to be more important included the location of the team base and the discipline of the team manager, although, interestingly, no previous work seems to have considered these.…”
Section: Community Mental Health Teams For Older People: a National Scontrasting
confidence: 55%
“…Top-down approaches to policy implementation are frequently criticised as they neglect to address the impact of front-line staff on the process (Hudson 2002). Lipsky (1980) describes the front line staff who interact directly with the public, act as "gate-keepers" to government services and draw on social and contextual resources to resolve the situations they face, as "street-level bureaucrats".…”
Section: Discussionmentioning
confidence: 99%
“…Partnership working is a central theme of the current UK Government"s "Third Way" policies (Hudson 2002) and aims to blur boundaries in order to provide seamless care across health and social care to patients (Hubbard and Themessl-Huber 2005). However, overcoming the barriers to joint working have been likened to demolishing the Berlin Wall .…”
mentioning
confidence: 99%
“…40,65,66 There are, however, a number of areas that would have required sensitive exploration and support, including the possibility that social work practitioners would perceive an increased emphasis on multidisciplinary assessment as a challenge to their authority and that nursing staff would view any involvement in discussions of charging and finances with concern. [66][67][68][69] Care plans are needed to support, sustain and enhance the quality of life of older people with mental health problems in their own home and to provide assistance to their carers The care planning function of care management encompasses the identification of the most appropriate means of meeting the needs/goals identified in the assessment and the securing of the necessary services/resources to meet them. 33 An important feature of intensive care management arrangements for older people with mental health problems is the number and breadth of services required to enable individuals to remain in their own homes.…”
Section: Care Management Should Be Provided By Members Of a Multidiscmentioning
confidence: 99%